Clarithromycin versus furazolidone for naïve Helicobacter pylori infected patients in a high clarithromycin resistance area. Issue 9 (10th March 2021) - Qiao, Chen; Li, Yueyue; Liu, Jing; Ji, Chaoran; Qu, Junyan; Hu, Junnan; Ji, Rui; Wan, Meng; Lin, Boshen; Lin, Minjuan; Qi, Qingqing; Zuo, Xiuli; et al.
Abstract: Background and Aim: The increase in antibiotic resistance makes the eradication of Helicobacter pylori more difficult. Considering the limitations of the application of susceptibility‐guided therapy, it is important to find an effective empirical regimen. The aim of the study is to compare the efficacy, safety, and cost‐effectiveness of clarithromycin‐based bismuth‐containing quadruple therapy (C‐BQT) and furazolidone‐based bismuth‐containing quadruple therapy (F‐BQT) in naïve H. pylori positive patients. Methods: This was an open‐label, randomized controlled, crossover trial. The trial comprised two phases. In C‐F group, patients received C‐BQT in the first phase; those who were still positive for H. pylori infection after the first phase entered the second phase to receive F‐BQT as rescue treatment. In F‐C group, patients were treated with F‐BQT firstly and rescued with C‐BQT. Results: As first‐line treatments, the eradication rates of C‐BQT and F‐BQT were 89.7% (157/175) and 92.0% (161/175) ( P = 0.458) in intention‐to‐treat analysis and 93.4% (156/167) and 95.8% (161/168) ( P = 0.327) in per‐protocol analysis, respectively. The cumulative eradication rates of the C‐F group and the F‐C group were both 94.3% in intention‐to‐treat analysis ( P = 1.000). Cost‐effectiveness indexes of F‐BQT and C‐BQT were 0.54 and 1.24 in first‐line treatments. Frequencies of adverse events in F‐BQT and C‐BQT had no differences (36.0% in C‐BQT vs 32.6% in F‐BQT, P = 0.499). Conclusions: Furazolidone‐based bismuth‐containing quadruple therapy should be preferred for its excellent cost‐effectiveness and acceptable safety.